ORGANIZATION IN SPORTS: A STUDY ON THE UTILIZATION OF THE “ORGANIZATION” TERM WITHIN THE BRAZILIAN SPORTING LEGISLATION. (Fiep Bulletin - online, 2015)
The organization term bears its origin from Greek, “organon”, which means instrument, utensil. The organization notion presents two (2) meanings: on one side it designates unities and social entities. Here Organization is understood as a physical constitution, enjoying relatively delimitated boarders, and which works on a relatively continuous basis, bearing in sight the carrying out of its objects. On the other side, (b) the same term designates certain social behaviors, in other words, the act or effect or organizing, an administrative function, such as: the act of organizing the activities within such Organizations. Since the publication of Decree-Law nr.: 3.199, of April 14th, 1941, mens legis has been seeking an answer from the legislative text and wishes its organization. Object: To analyze the frequency and the utilization of the organization term within the main terms of the sporting legislation. Methodology: The present study has been performed bearing a classified approach as Administrative, which is utilized for the qualitative researches within the Sporting Sciences in the area of the Organization / Management, and bearing a methodological approach of the dialectical descriptive type, producing as its final results, by means of the quantitative summaries, the diverse forms for the utilization of the organization term.  Study delimitation: The present study has been delimited within the analysis as of Law nr.: 6.251/75 until Decree nr.: 2.574/98 which regulates Law nr.: 9.615/98  “Pelé's Law”, in other words, of all the Laws and Decrees that used to regulate and regulate the Brazilian sport since 1975. Results: The organization term becomes an interrupted seek for rendering concrete the phenomenon within the sport. It has been perceived as the time elapses that there is a decrease in its employment either as an administrative unity or as an administrative function. Main Conclusions: With the re-establishment of the democratic status of right and the promulgation of the Brazilian Constitution, the sporting community understanding has demonstrated that the organization does not come nor it arises from the legislative texts, but from the intrinsic and extrinsic values from the sporting phenomenon.
Keywords: .